Caracterização mecânica do carvão vegetal de clones de Corymbia - Costa, Luciano Junqueira (2016)
Steel industry is the largest consumer of charcoal in Brazil. However, one of the main issues faced by this sector is the heterogeneity presented by the charcoal, with physical, chemical and mechanic properties directly influenced by the final temperature of carbonization. For the physical and chemical properties, there are well-defined norms for analysis. However, there are no specific norms for evaluating the mechanical properties, and the tests currently used are not efficient to evaluate product quality. This work had the objective of mechanically evaluating the quality of charcoal of Corymbia clones produced at the carbonization temperatures of 350, 450, 550 and 700 o C. The influence of temperature over carbonization yield, as well as physical, chemical and energetic properties of the charcoal, were also evaluated. For this, seven clones of the Corymbia genus were collected from northern Minas Gerais, Brazil. Wood logs were removed from the trunk at a height of 1.3m, processed and carbonized. Subsequently, we prepared samples of the coal used in the compression trials, parallel and perpendicular to the coal fibers. With the results obtained, we verified that the final carbonization temperature significantly influenced carbonization yields, as well as the physical, chemical, energetic and mechanical properties of the charcoal. For the mechanical trials, we verified an increase in the characteristics of elasticity and resistance of the charcoal for parallel and perpendicular compression at a temperature of 700 o C, with the highest values verified for compression parallel to the fibers.